THE COMPUTATION OF THE OIL SPREADING IN THE BINH THUAN COASTAL ZONE - Phung, Nguyen Ky; Bay, Nguyen Thi (Vietnam Journal of Marine Science and Technology, 2008)
In this paper, the authors present the 2D numerical model to simulate the currents by tide and by wind and the spreading, disintegration of the oil stain. In the model, the evaprotion, dissolution, emulsion and diffusion processes are calculuted. The model is applied to simulate the oil spreading process in the Binh Thuan coastal zone.